An updated review on factors and their inter-linked influences on photovoltaic system performance. Issue 9 (September 2018) - Rao, Roshan R.; Mani, Monto; Ramamurthy, Praveen C.
Abstract: Globally installed solar photovoltaics (PV) capacity has crossed three hundred gigawatts and is increasing each year. As the share of solar PV in the energy mix of a country increases, forecasting PV power available will be crucial. To forecast the instantaneous and long-term PV power output, understanding the factors influencing them is necessary. In this view, this work elaborates on the factors that impact the PV system through tabulation and graphical explanation. Further, a discussion of the articles related to the dust-induced change in performance is made. To understand the impact of dust on solar PV systems in depth, advanced instrumentation and methodologies have been used in the past few years. One of the methods is the measurement of spectral transmittance/reflectance/absorptance of the dust layer on the PV panel. This has led to the question whether a thin layer of some specific dust can be beneficial by absorbing infrared (IR) heat and hence allowing the PV cells to operate at a lower temperature. Many controlled experiments in the laboratory have been made using the artificial dust and sun simulators; and such studies aid in the development of numerical models. Research in modeling, mathematical analysis (from first principles) of dust deposition, and calculation of its impact on panels have been given importance in recent years. Outdoor experiments are relatively more common than other modes of research in this field. Studies involving the interaction of deposited dust with spectral radiation, improving the correlation between artificial and natural dust deposition, the interplay between dust and atmospheric parameters are to be encouraged.